(untitled) (Spectrum Journal of Innovation, Reforms and Development, 2026)
This article analyzes innovative methods for developing students’ speech activity within the higher education system. It highlights the linguistic, psychological, and pedagogical foundations of forming speech activity, and examines the role of interactive, digital, and multi-component educational technologies in enhancing speech competencies.